Pengembangan Evaluasi Pembelajaran PAI di Era Modern pada kampus Politeknik Berbasis Pemikiran Imam Al Ghazali - Qolbi, Satria Kharimul (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
The rapid integration of digital technology into Islamic education presents new challenges to the effectiveness of assessment systems, particularly in Islamic Religious Education (PAI). Existing evaluation models often emphasize cognitive outcomes while neglecting affective and spiritual dimensions, which are central to Islamic education. This study aims to explore the contribution of Imam Al-Ghazali’s educational thought in formulating a more holistic and contextually relevant evaluation model for PAI in the modern era, especially within polytechnic institutions. Using a qualitative approach through library research, this study analyzes Al-Ghazali’s classical works and related academic literature. The findings indicate that Al-Ghazali’s evaluation model, which integrates cognitive, affective, and psychomotor aspects and emphasizes Sufi-based values such as worship habituation, self-reflection, control of desires, and moderation, remains highly applicable to today’s digital learning environment. This approach shows that value-based assessment can not only measure academic achievement but also support the formation of students’ character and ethical integrity. The study contributes conceptually to the development of integrative Islamic education evaluation models and recommends further empirical research to validate its practical implementation across various educational levels. Such efforts are essential to align Islamic education with the demands of the digital era while preserving its foundational moral and spiritual objectives.